Battery state of health (SOH) assessment using KVI's battery analyser BA-2000 - Tey, Bryan Jun Hong (Nanyang Technological University, 2022)
In the field of energy storage systems, batteries are often used in numerous daily applications. One of the most common yet important issue is the evaluation of the battery lifespan so that its cells can be better optimized, and actions can be taken to either mitigate the degradation or replace it altogether. There are several methods to obtain this piece of information and this report aims to evaluate the advantages of using thermodynamics over complex algorithms and data analytic models.